Pengendalian Persediaan Bahan Baku Kedelai Menggunakan Metode EOQ (Economic Order Quantity) Pada Kopti Kabupaten Bogor - Deni Rahman; Fathiya Najmaayyubi; Hasna Salsabila; Rachmawati Rezeki; Noviqa Shaumi; Agung Prayudha Hidayat; Astiani Safitri (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The need for soybeans in Indonesia increases along with population growth, with demand reaching 2.7 million tons in 2023. Soybeans are an important raw material in the food industry, especially for processed products such as tempeh. This research aims to analyze the control of soybean supplies in the Bogor Regency Tofu and Tempe Cooperative (KOPTI) using the Economic Order Quantity (EOQ) method. The Economic Order Quantity (EOQ) method was chosen because it is able to optimize the costs of ordering and storing raw materials. Primary data was obtained through interviews with KOPTI owners and employees. The analysis results show that the optimal order quantity is 333,371 kg with an order frequency of 4 times per year. In addition, the safety stock required is 82,252 kg, and the reorder point is 85,865 kg. Using the EOQ method can save total inventory costs from IDR 14,332,491.57 to IDR 910,102.39. This research suggests KOPTI to apply the Economic Order Quantity (EOQ) method to increase cost efficiency and maintain stable raw material supplies.